Non albicans Candidemia: an emerging menace in neonatal intensive care unit - Shettigar, Chandrashekar G.; Shettigar, Sanchita (International Journal of Contemporary Pediatrics, 2018)
Background: Candidemia has become an increasingly major problem in neonatal intensive care unit (NICU) which is associated with high mortality and morbidity. In this study we evaluated the epidemiology of Candidemia in neonates who were admitted to NICU and their in vitro susceptibility to commonly used antifungal drugs. Methods: This was a retrospective study of candidemia in NICU from October 2014 to September 2017. The isolates were identified as per standard mycological techniques and antifungal susceptibility was determined by disk diffusion method. Results: Out of 563 blood culture analyzed, 54(9.59%) culture yielded Candida in their blood. The non albicans Candida (NAC) species were the predominant organism for candidemia in neonates, accounting for 35 (64.81%) and the remaining 19 (35.18%) isolates were of C. albicans. Among the NAC species, the maximum isolates were of C. krusei (31.48%) followed by C. glabrata (22.22%). Non albican Candida were more resistant to azole group of antifungal, especially commonly used antifungal like fluconazole (51.43%). Among NAC species, C. glabrata was most resistant and C. tropicalis was least resistant organism. Prematurity <34 weeks, very low birth weight (<1500gm), prolonged use of broad spectrum antibiotic therapy, prolonged use of central venous catheter, mechanical ventilation, parenteral nutrition, prolonged NICU stays and concomitant bacterial sepsis were significantly associated with Candida infection in blood stream. NAC species were also associated with high mortality rate. Conclusions: Increased incidences of candidemia along with emergence of NAC species have become an important health care issue. Therefore, knowledge of local epidemiological data on candidemia is essential which will guide on therapeutic decision making.